2014
DOI: 10.1111/jnc.12718
|View full text |Cite
|
Sign up to set email alerts
|

PI3K‐p110‐alpha‐subtype signalling mediates survival, proliferation and neurogenesis of cortical progenitor cells via activation of mTORC2

Abstract: Development of the cerebral cortex is controlled by growth factors among which transforming growth factor beta (TGFb) and insulin-like growth factor 1 (IGF1) have a central role. The TGFb-and IGF1-pathways cross-talk and share signalling molecules, but in the central nervous system putative points of intersection remain unknown. We studied the biological effects and down-stream molecules of TGFb and IGF1 in cells derived from the mouse cerebral cortex at two developmental time points, E13.5 and E16.5. IGF1 ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 46 publications
(52 reference statements)
2
41
0
Order By: Relevance
“…Little is known about upstream and downstream effects of mTORC2, but it has been suggested to be directly or indirectly activated by PI3K (42)(43)(44)(45)(46). VHL-deficient RCC cells that constitutively express HIF2a have been shown to have differential dependency on mTORC1 and mTORC2 for HIF1a and HIF2a protein expression (20).…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about upstream and downstream effects of mTORC2, but it has been suggested to be directly or indirectly activated by PI3K (42)(43)(44)(45)(46). VHL-deficient RCC cells that constitutively express HIF2a have been shown to have differential dependency on mTORC1 and mTORC2 for HIF1a and HIF2a protein expression (20).…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, FOXG1 and FOXO proteins might be a node of intersection between TGFβ- and IGF-signaling pathways. In contrast to this view, we recently reported that IGF1-signaling activates cell proliferation in early cortical development (E13.5), whereas TGFβ-signaling is mainly active at later stages (E16.5) [2]. Hence, FOXG1 and FOXO proteins might be cofactors that are implicated in different developmental responses to IGF1- and TGFβ-signals rather than nodes of intersection.…”
Section: Introductionmentioning
confidence: 96%
“…Since proliferation and differentiation take place simultaneously in developing organ systems, cellular interpretation of such signals has to occur cell autonomously, for example through activity of specific transcription factors. Transforming growth factor β (TGFβ) is an extrinsic cue implicated in neuronal differentiation of cortical progenitor cells (CPCs) [1, 2]. It has 3 different isoforms (TGFB1, 2, and 3) and is a member of the TGFβ superfamily, including Bone morphogenetic proteins (BMPs) and Activins.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that PI3K/Akt signaling regulates proliferation and inhibits differentiation of adult neural progenitors (Peltier et al, 2007). Inhibition of PI3K-p110α also interferes with cell proliferation, survival and neuronal differentiation through mTORC2 activation (Wahane et al, 2014). Besides the possible role of PI3Kγ in neurogenesis, the reduced number of DCX + cells in PI3Kγ −/− mice could also reflect the increased death of these cells.…”
Section: Discussionmentioning
confidence: 96%